C-C Motif Chemokine Ligand 2 (CCL2) Mediates Acute Lung Injury Induced by Lethal Influenza H7N9 Virus - Lai, Chengcai; Wang, Keyu; Zhao, Zhongpeng; Zhang, Liangyan; Gu, Hongjing; Yang, Penghui; Wang, Xiliang (Frontiers in Microbiology, 2017)
An avian-origin influenza A (H7N9) virus was a cause for concern in China in the spring of 2013. Most H7N9 infections resulted in acute respiratory distress syndrome (ARDS), which is a severe form of acute lung injury (ALI) that contributes to morbidity and mortality. In this study, we induced viral ALI by infecting wild-type and CCL2-deficient mice with influenza H7N9 virus. The results suggested a close association between C-C motif chemokine ligand 2 (CCL2) expressions and ALI induced by a lethal H7N9 virus strain (A/Hebei/01/2013). Elevated CCL2 levels were also detected in confirmed human cases of H7N9 and the bronchoalveolar lavage fluid of H7N9-infected mice. Moreover, CCL2 was overexpressed in the lung tissue of infected mice. More importantly, CCL2 deficiency ameliorated H7N9-induced ALI in mice as determined by weight loss, survival rate, the wet:dry ratio of the lung, and pathology. Taken together, our findings demonstrate that CCL2 is essential for H7N9 virus infection and thus that it is a potential therapeutic target for influenza.